Foreign aid for capacity-building to address climate change: Insights and applications - David Victor (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The paper examines the role of foreign aid in building capacity to address climate change. While the experience with this topic is relatively recent and not yet extensive, analogous questions have arisen in many other areas of foreign aid. It is likely that climate change aid programmes work best in countries with well-functioning systems of public administration, sound management of public finances, and independent media that hold government accountable for performance - all factors widely known to make other aid programmes more effective and adaptive. As countries try to expand climate aid quickly, historical patterns suggest bilateral aid - which is easier for donors and recipients to control - is likely to expand much more than multilateral aid. A shift is also likely from an emphasis on mitigation of emissions to a growing role for adaptation. Expanding climate aid must confront what I call the 'aid paradox' which is that the conditions of national capacity under which aid is most likely to be effective are least likely to be present in the countries that are most in need of foreign aid because they cannot raise needed funds on their own.
Keywords: A12; D02; O19; Q54; 330; climate change impacts; agriculture; sea level; climate impacts assessment; development aid